Symmetric systems of Van Der Pol equations - Balanov, Zolman; Farzamirad, Meymanat; Krawcewicz, Wiesław (Topological Methods in Nonlinear Analysis, 2006)
We study the impact ofsymmetries on the occurrence of periodic solutions in systems of van der Pol equations. We apply the equivariantdegree theory to establish existence results for multiple nonconstant periodic solutions and classify their symmetries. The computations of the algebraic invariants in the case of dihedral, tetrahedral, octahedral and icosahedral symmetries for a van der Pol system of equations are included.